Who is wellness for? : an examination of wellness culture and who it leaves behind - Róisín, Fariha (Harper Wave, an imprint of HarperCollinsPublishers, 2022)
In this thought-provoking book, part memoir, part journalistic investigation, the acclaimed writer and poet, a Muslim queer Bangladeshi, reveals how wellness culture has become a luxury good built on the wisdom of Black, brown and Indigenous people--while ignoring and excluding them.